Transparent conducting oxide based devices - O'Sullivan, Marita Kay (Trinity College (Dublin, Ireland). School of Physics, 2011)
Transparent conducting oxide (TCO) materials, formerly regarded as degenerate conductors of only one carrier type, can now be considered as transparent semiconductors possessing the potential for integration into more sophisticated transparent electronic settings. A general description of this class of materials is presented in the introductory chapter, setting the objectives of the dissertation as a natural progression from material preparation and characterisation towards device design and prototyping.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.